Development and implementation of a worksite-based intervention to improve mothers' knowledge, attitudes, and skills in sharing information with their adolescent daughters on preventing sexual violence: lessons learned in a developing setting, Sri Lanka - Dilini Mataraarachchi; P.K. Buddhika Mahesh; T.E.A. Pathirana; P.V.S.C. Vithana (BMC, 2024)
Abstract Background Sexual violence among adolescents has become a major public health concern in Sri Lanka. Lack of sexual awareness is a major reason for adverse sexual health outcomes among adolescents in Sri Lanka. This study was intended to explore the effectiveness of a worksite-based parent-targeted intervention to improve mothers' knowledge, and attitudes on preventing sexual violence among their adolescent female offspring and to improve mother-daughter communication of sexual violence prevention with the family. Methods "My mother is my best friend" is an intervention designed based on previous research and behavioral theories, to help parents to improve their sexual communication skills with their adolescent daughters. A quasi-experimental study was conducted from August 2020 to March 2023 in randomly selected two Medical Officer of Health (MOH)areas in Kalutara district, Sri Lanka. Pre and post-assessments were conducted among a sample of 135 mothers of adolescent girls aged 14-19 years in both intervention and control areas. Results Out of the 135 mothers who participated in the baseline survey, 127 mothers (94.1%) from the intervention area (IA) physically participated in at least one session of the intervention. The worksite-based intervention was effective in improving mothers' knowledge about adolescent sexual abuse prevention (Difference in percentage difference of pre and post intervention scores in IA and CA = 4.3%, p = 0.004), mother's attitudes in communicating sexual abuse prevention with adolescent girls (Difference in percentage difference of pre and post intervention scores in IA and CA = 5.9%, p = 0.005), and the content of mother-daughter sexual communication (Difference in percentage difference of pre and post intervention scores in IA and CA = 27.1%, p < 0.001). Conclusions and recommendations Worksite-based parenting program was effective in improving mothers' knowledge about sexual abuse prevention among adolescent daughters and in improving the content of mother-daughter communication about sexual abuse prevention. Developing appropriate sexual health programs for mothers of different ethnicities, and cultures using different settings is important. Conduction of need assessment programs to identify the different needs of mothers is recommended.